The Dilemma of Dissidence - Louw-Potgieter, Joha (PINS-Psychology in Society, 1987)
Disaffiliation from a group affects the very essence of group belongingness for those who choose to remain within the group. It heightens the salience of group norms, raises questions about the validity of these norms, the value of group membership and might even affect ingroup solidarity and determine the course of action to be taken against the non-conforming group member. The aim of this paper is to point out that those individuals who wish to retain the status quo, be they laypersons or professionals, will seek to locate the origin of dissidence within the non-conforming individual, thereby accepting the group and its norms uncritically as a given.